PENGARUH INTELECTUAL CAPITAL DISCLOSURE TERHADAP NILAI PERUSAHAAN DAN HARGA SAHAM - Ifki Dutrianda; Hisar Pangaribuan (Jurnal Ekonomis, 2020)
This study aims to determine the effect of intellectual capital disclosure on firm value and also the effect of intellectual capital disclosure on stock prices in Indonesia. The sample selection method used in this study was purposive sampling. Of the 43 banks in Indonesia, it was found that there were 40 banks that were sampled in this study according to the specified characteristics. This study uses secondary data derived from annual reports of banking companies on the Indonesia Stock Exchange for the 2017-2019 period. Data processing is done using the STATA application. Measurement of disclosure of intellectual capital uses checklist items, measurement of company value uses the price to book value and stock prices are seen from the stock market closing price contained in the annual report. The results of this study indicate that an increase in the disclosure of intellectual capital cannot significantly affect the increase in firm value, while on the same occasion an increase in disclosure of intellectual capital information itself can significantly affect an increase in stock prices.